Antiandrogenic effect of perinatal exposure to the endocrine disruptor di-(2-ethylhexyl) phthalate increases anxiety-like behavior in male rats during sexual maturation - Carbone, Silvia Elena (2013)
Di-2-ethylhexyl phthalate (DEHP) is the most widely used phthalate to convey flexibility and transparency to plastic products made of polyvinyl chloride. It has been recognized as endocrine disruptor and associated with reproductive toxic effects. We examined the effects of perinatal exposure to DEHP on anxiety-like behavior, using the Elevated Plus Maze (EPM) test, in male and female rats at different stages of sexual development. Anxiety-like behavior was expressed as a) frequency of open arm entries over the total arm entries (% FEO); b) time spent in them compared with total time the animal stayed in the EPM (% TSO) and c) time spent in closed arms (TSC). Because DEHP has anti-androgenic action we also tested control and exposed immature male rats pretreated with testosterone. We found sex differences in behavior induced by DEHP; while male rats of 45 and 60 days of age showed a significant decrease in FEO and TSO percentages, as well as an increase in TSC, no changes were observed in anxiety-like behavior in perinatal DEHP exposed females at these ages of sexual maturation. In 60-day-old male rats, DEHP exposure produced a significant decrease in serum testosterone levels. Testosterone replacement was able to antagonize the adverse effects of DEHP exposure on LH, activating the negative feed-back mechanism of this steroid on reproductive axis, as well as increasing FEO and TSO percentages to similar values observed in the control group. These findings suggest that the anti-androgenic action of this chemical could be one possible mechanism underlie anxiogenic-like behavior produced by perinatal DEHP exposure in 60-day-old male rats.